The rates of middle molecules in the blood in rats with different motor activity in alcoholic and non alcoholic exerimental hepatosis - Denefil, O. (Journal of Education, Health and Sport, 2021)
Alcohol use disorders affect millions of individuals worldwide. The impact of these facts lies in the elevated social and economic costs. Liver metabolizes 75-98 % of ethanol that enters the organism. If the level of alcohol in the liver cells exceeds its degradation rate, alcoholic liver disease develops. The aim of the study was to determine the peculiarities of hepatotoxicity after simulation of of ethanol hepatosis and non-alcoholic steatohepatitis of high and low-motor active rats. Material and methods of investigation. The experiments were performed on on 72 white outbred male rats. The animals were divided into three groups: control, non-alkoholic hepatitis (NAH), ethanol hepatosis (EH). Each of group was subdivided – animals with high and low-motor activity (HA and LA). Contents of middle-mass molecules (MMM) were determined in the blood serum. Results. The analysis of the results shows that the levels of MMM in blood serum are increasing. Dystrophic changes that appear in a consequence of hypoxia are noted in NAH and EH. Both morphological and biochemical changes were more significant in HA animals. The degree of MMM accumulation depends on the severity of the pathology and motor activity of the animals. Less activity of MMM238 is observed in HA rats, which can be explained by the development of multi-organ pathology. Conclusions. During our investigations it was found the significant increasing of MMM levels in blood serum in rats with ethanol hepatosis and nonalkoholic hepatitis. The accumulation of MMM is not only a marker of endotoxication, they also increase the course of the pathological process, acquiring the roles of secondary toxins, affect the viability of all organs and systems. The degree of MMM accumulation depends on the moto activity of the animals and simulated pathology and is more significant in highly active animals, compared with low-active in the ethanol using. Less activity of MMM238 is observed in HA rats with EH, which can be explained by the development of multi-organ pathology, in particular, renal impairment. Morphological investigations showed that the grade of liver injury was more significant in HA rats.